Correlation of Liver Enzymes with Ultrasound Grading in Patients with Non-alcoholic Fatty Liver - Azeez Mhana Khalaf; Dhamiaa Maki Hamza; Alaa S. Alattab; Saad Hasan Talib Al-allak; Ziyad Saleem Mousa; Zainab Abdulkareem Mohammed (Karbala Journal of Medicine, 2025)
Background: Nonalcoholic fatty liver disease (NAFLD) is a leading cause of liver disease worldwide and is projected to become the foremost cause of end-stage liver disease, affecting both adults and children. This study evaluated the association between ultrasound-based NAFLD grading and changes in liver enzymes: alanine aminotransferase (ALT), aspartate aminotransferase (AST), total serum bilirubin (TSB), triglycerides (TG), and cholesterol (CH). Methods: A case-control study was conducted between December 2024 and March 2025, involving 176 participants. The study population was divided into two groups: 100 patients diagnosed with NAFLD and 76 healthy individuals serving as controls. Diagnosis and grading of NAFLD (mild, moderate, and severe) were based on ultrasonography and biochemistry analysis. Results: Biochemical analysis revealed significant differences between NAFLD patients and healthy controls, as well as across the different NAFLD grades. ALT, AST, TSB, TG, and CH levels were significantly elevated in NAFLD patients compared to healthy controls (p =0.001 for all parameters). A progressive increase in these biochemical markers was observed as disease severity advanced. Among the NAFLD grades, grade 2 was the most commonly observed. Post-hoc Least Significant Difference (LSD) tests confirmed significant differences in these parameters between all NAFLD grades (p = 0.05), indicating worsening hepatic and metabolic dysfunction throughout disease progression. Conclusions: Serum levels of ALT, AST, TSB, TG and CH showed a positive correlation with NAFLD severity, reflecting the underlying pathophysiological progression of the disease. These biochemical markers may serve as valuable adjuncts to non-invasive diagnostic tools such as ultrasound, which is commonly used for initial detection and grading of hepatic steatosis. When used alongside advanced modalities like transient elastography (FibroScan), they can enhance disease staging accuracy and support more targeted clinical management strategies. Keywords: NAFLD, AST, ALT, bilirubin, triglyceride, cholesterol